ELIMINATION D’ALUMINIUM PAR DES SUPPORTS PREPAREES A PARTIR DE DEUX ALGUES MARINES : SARGASSUM MUTICUM (YENDO) FENSHOLT, 1955 ET CYSTOSEIRA TAMARISCIFOLIA (HUDSON) - Ould abdellahi Lella; Elyahyaou Ouafae; Kerrouri Saloua; Sammama Amal; Bouabid Bahia; Bengueddour Rachid (European Scientific Journal, ESJ, 2015)
The ore loading and the rejected wastes in Nouadhibou port cause major problems threatening the bay of the Star. So, several national and international sectors (associations, Ministers, Universities,...) are heading the search for appropriate solutions to minimize the dangers of this problem. To contribute to these solutions, we have prepared homogenates of two algae Sargassum muticum and Cystoseira tamariscifolia. Also, metal solutions were prepared by simply dissolving aluminum nitrate in distilled water. Then, the seaweed shreds were put in contact with the aluminum solutions and the systems were stirred, the solutions are then filtered and the filtrate is analyzed by ICP (Inductively Coupled Plasma). The results obtained during the kinetics of aluminum adsorption ambient conditions have shown that shreds of Cystoseira and Sargassum algae muticum tamariscifolia have extremely large capacities for adsorbing aluminum. This was confirmed by the textural analysis through analysis by scanning electron microscopy, fluorescence spectrometry analysis X, as well as infrared spectroscopy of the supports before and after contacting with the metal. Thereby, Cystoseira tamariscifolia and Sargassum muticum could be used as an alternative solution to protect the bay of the “Star” especially these two algae lives naturally in the aquatic ecosystem of the region.